Manufacturing and management paradigms, methods and tools for sustainable Industry 4.0-Oriented Manufacturing Systems - Varela, M.L.R. (2022)
[Excerpt] In the current Industry 4.0 era (I4.0, for short) [1–3], manufacturing and management (M&M) paradigms, methods and tools should be wisely developed to fulfil sustainability issues, regarding not just economic but also social and environmental concerns by simultaneously fostering organizational efficiency excellence and transformational initiatives, therefore contributing to enduring business results [4].